Acta Soc. pro Fauna et Flora Fennica. - Societas pro Fauna et Flora Fennica; Societas pro Fauna et Flora Fennica (Helsinki, Societas., 1875)
Vol. 68 is "Index generum et specierum quae operibus a Societate pro Fauna et Flora Fennica separatim editis continentur."
Title varies slightly.
English, Finnish, German, Norwegian or Swedish.
Vols. 1-60, 1875-1937 issued as v. 61.
Vol. 64 is an index to: Societas pro Fauna et Flora Fennica. Notiser ur Shallskapets pro Fauna et Flora Fennica förhandlingar, and: Societas pro Fauna et Flora Fennica. Meddelanden af Societatis pro Fauna et Flora Fennica.
Keywords: Natural history